Using biomonitoring to assess the ecological state of soil in a technologically loaded area - Cherniak, L.M.; Proskurnia, O.I.; Mikhieiev, O.M.; Dmytrukha, T.I. (Problems of Environmental Biotechnology, 2023)
The aim of the study was to investigate the dependence of the growth characteristics of different plant species on the type of oil product that enters the soil.